2016
DOI: 10.1097/hjh.0000000000000886
|View full text |Cite
|
Sign up to set email alerts
|

Soluble dipeptidyl peptidase-4 induces microvascular endothelial dysfunction through proteinase-activated receptor-2 and thromboxane A2 release

Abstract: In summary, these findings reveal sDPP4 as a direct mediator of endothelial dysfunction, acting through PAR2 activation and the release of vasoconstrictor prostanoids. By interfering with these actions, DPP4 inhibitors might help preserving endothelial function in the context of cardiometabolic diseases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
1
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 30 publications
1
36
1
6
Order By: Relevance
“…As a consequence, induction of vascular inflammation, endothelial dysfunction and smooth muscle cell proliferation takes place. These processes are hallmarks of vascular diseases and have been linked to PAR2 (Hirano and Kanaide, 2003; Wronkowitz et al, 2014; Romacho et al, 2016). To our knowledge, there are scarce reports about a direct connection between obesity and PAR2 in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a consequence, induction of vascular inflammation, endothelial dysfunction and smooth muscle cell proliferation takes place. These processes are hallmarks of vascular diseases and have been linked to PAR2 (Hirano and Kanaide, 2003; Wronkowitz et al, 2014; Romacho et al, 2016). To our knowledge, there are scarce reports about a direct connection between obesity and PAR2 in the vasculature.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we have focused on the effects of CM on inflammation and proliferation as two key processes in atherogenesis, since the role of PAR2 in adipokine-induced impairment of vascular reactivity (Romacho et al, 2016) and the effect of CM on endothelial migration has already been proven (Hu et al, 2013). CM contains numerous molecules derived from adipocytes, which serve as potential ligands for PAR2, thereby contributing to promote PAR2-mediated effects, such as proliferation.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, increased plasma DPP-4 activity accompanies adipose tissue expansion in humans, rats, and mice (Kirino et al, 2009;Lamers et al, 2011;Mulvihill et al, 2017;Zhuge et al, 2016). Moreover, small interfering RNA-mediated depletion of Dpp4 from human primary adipocytes improved adipocyte insulin sensitivity (Rohrborn et al, 2016), whereas treatment with sDPP4 directly activated inflammatory signaling pathways ex vivo (Lee et al, 2016;Romacho et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Circulating form of DPP‐4 can impair vascular reactivity by causing defective endothelium‐dependent vasodilation, which contributes to endothelial dysfunction. Soluble DPP‐4 is agonist for protease‐activated receptor 2 on vascular cells, activator of downstream cyclooxygenase and promoter of endothelial release of vasoconstrictor thromboxane A2 . It was shown that soluble DPP‐4 in concentration‐dependent manner activates extracellular signal‐regulated kinase (ERK) 1/2, induces phosphorylation of the nuclear factor kappa B (NF‐κB) subunit p65, increases inducible nitric oxide synthase (iNOS) activity, expression and secretion of proinflammatory cytokines, interleukin (IL)‐6, ‐8, monocyte chemoattractant protein‐1 (MCP‐1), and stimulates proliferation of human vascular smooth muscle cells.…”
Section: Introductionmentioning
confidence: 99%